The participants experience of masses sports event in pandemic period. Taking marathon runners as an example - Xu, X. (Advances in Economics, Business and Management Research, 2022)
With the suspense of the pandemic of COVID-19 in 2020, leisure sports events are being canceled most of the time all over the world. This study used multiple methods and data to examine runners` embodiment experience, aimed at discussing the current situation about marathon runners and marathon event tourism, and figuring out the motivation of runners` activities under the pandemic through direct observation and interviews from their daily life. The results showed runners` experience in marathon training, marathon race, and stretch-out process separately, indicating that running for a marathon could decrease mental stress, and the combination of body and mind helps runners face little depression during the pandemic. This study also provides suggestions for event organizations to focus on event design and services from runners` point of view.